Symposium 3: Networked learning in the time of pandemic: Intersubjectivity and alienation - du Toit, Jean; Swer, Gregory (Proceedings of the International Conference on Networked Learning, 2024)
Digital networking technologies have allowed lecturers and students to remain connected while being physically isolated during global lockdowns resultant from the COVID-19 pandemic. We argue that the increased utilization of online spaces for teaching and learning during the time of isolation has brought the question of intersubjectivity and alienation in cyberspace to the forefront. As part of an ongoing phenomenological analysis of the virtual, we survey the experiences of networked learning reported by a group of South African university students in their end of course surveys. We track particularly their experience of alienation, their capacity to engage with material in the online environment, and their awareness of self as a learner. For Merleau-Ponty there resides in intersubjectivity a founding corporeity that serves to explicate the composition of the intersubjective world as based in a plurality of anonymous subjects and in the intersubjectivity of intellectual consciousnesses. In terms of the virtual, a redeployment of Merleau-Pontian thought (and particularly his concept of the flesh) reveals that the body-subject and digital technology artefact are co-implicit in the generation of the virtual. The virtual serves as a point of networked intersubjectivity that concretely expands and constrains human experience and behaviour. Furthermore, in the virtual we navigate a reified landscape. Virtual reification, though seemingly a contradiction, sees us treating the virtual as concrete from the basis of our embodiment. This leads us to an alienated networked intersubjectivity, whereby all potentialities are founded in ordered and carefully arranged systems that promulgate pragmatic and capitalist logics. We investigate how reification makes up the virtual, and how our engagement with the virtual points us back to the nature of alienation (indeed, for Marx, alienation is an intersubjective social relation). We find in the virtual therefore not isolation, but rather a deficient mode of intersubjectivity. While the individual never becomes atomized, for even in the virtual a deficient mode of intersubjectivity remains nevertheless a mode of intersubjectivity, we find that the individual functions as part of a deficient and distorted network. We suggest in conclusion certain teaching methods that may minimize or mitigate students’ experience of alienation.